Manajemen Pembelajaran Bahasa Arab Berbasis TIK di Madrasah Aliyah Daarul Uluum Majalengka - Badrudin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
This study aimed to analyse the management of ICT-based Arabic learning. This study was designed to find the management of ICT-based Arabic learning in MA Daarul Uluum Majalengka. This study proposed that the integration between various fields of studies and ICT, including Arabic language learning, is urgently needed in this digital era. However, there are a number of problems experienced by some institutions, such as the absence of clear format on the use of ICT in the effort of integrating both disciplines. This study applied a qualitative research approach with descriptive research method. The data were collected by conducting observation, interview, and documentation. The data were analysed using the qualitative analysis techniques. The results showed that the design of ICT-based Arabic learning model which can be developed at MA Daarul Uluum Majalengka is a communicative computer-based Arabic learning model. This model is implemented through setting the objectives, selecting the materials and the media, and developing evaluation procedures. The materials and other learning tools are designed using computer programs. Through this learning model, teachers served as learning motivator and facilitator elaborating the materials that need further clarification